The influence of social support provider on adolescent athlete burnout and engagement - Mellano, K. T.; Pacewicz, C. (Journal of Clinical Sport Psychology, 2023)
The purpose of the current research was to examine the interaction of teammate and coach support on athlete burnout and engagement, and determine how type of teammate and coach support links with athlete burnout and engagement. Adolescent athletes (N = 176) completed measures of support, burnout, and engagement. Total teammate and coach support accounted for 14.9%-26.0% and 22.4%-36.7% explained variance across dimensions of burnout and engagement, respectively. No meaningful significant interaction was found. Teammate esteem support predicted reduced accomplishment, devaluation, confidence, and vigor (ß = -0.31, -0.36, 0.28, and 0.28), while emotional and tangible support predicted dedication (ß = 0.29 and 0.20) and enthusiasm (ß = 0.30 and 0.22). Coach esteem support predicted reduced accomplishment (ß = -0.59) and devaluation (ß = -0.27). Findings suggest that support from one key agent can enhance youth athlete well-being, but types of support provided by agents differ in salience.